Bilateral giant macular holes: A rare manifestation of Alport syndrome. Issue 1 (January 2019) - Raimundo, Miguel; Fonseca, Cristina; Silva, Rufino; Figueira, João
Purpose: Alport syndrome is a rare condition characterized by the clinical triad of nephritic syndrome, sensorineural deafness, and ophthalmological alterations. Herein, we present a rare case of a patient diagnosed with Alport syndrome and bilateral giant macular holes. Case description: A 40-year-old woman with a previously unreported mutation in the COL4A4 gene suggestive of autosomal-recessive Alport syndrome presented at our department. The patient exhibited bilateral full-thickness macular holes measuring >1500 µm at their smallest diameters. The very large dimensions of both macular holes were indicative of a bad prognosis regarding hole closure, and a conservative approach was adopted. The patient was maintained on renal substitution therapy, and genetic counseling was offered to other family members. Conclusion: Ophthalmological findings associated to Alport syndrome commonly include anterior lenticonus and dot-and-fleck retinopathy, although giant macular holes can also be associated with this condition. A multidisciplinary approach is crucial in the management of these patients, as Alport syndrome is an inherited systemic basement membrane disease.